Association Between Social Media Use and Burnout Among Primary Health Care Workers During the COVID-19 Pandemic in China: Nationwide Cross-Sectional Survey - Jie Gu; Ping Zhu; Yijing Chu; Yuge Yan; Yuqi Yang; Jing Guo; Biao Xi; Shanzhu Zhu; Hong Liang; Jiewen Xiao; Jiaoling Huang (Journal of Medical Internet Research)
Abstract BackgroundThe COVID-19 pandemic has intensified health care worker burnout and increased their engagement with social media. However, it remains unclear whether social media is beneficial in mitigating burnout among primary health care workers (PHWs). ObjectiveThis study aims to report the prevalence of burnout among Chinese PHWs and investigate the relationship between social media use, specifically WeChat Moments usage, and burnout, with a focus on urban-rural differences. MethodsOur nationwide cross-sectional survey was conducted between May and October 2022 and included 3769 PHWs. Burnout was assessed using the Maslach Burnout Inventory-Human Services Survey, and WeChat Moments usage was self-evaluated. Weighted data were used to report the prevalence of burnout nationwide and in urban and rural areas. Multivariate logistic regression and subgroup analyses were used to examine the association between burnout and WeChat Moments usage frequency, highlighting differences between urban and rural PHWs. ResultsUrban PHWs reported a higher prevalence of burnout compared with their rural counterparts (212/1200, 17.6% vs 351/2569, 13.7%; PPPP ConclusionsUrban and rural differences in burnout prevalence were observed among PHWs, with urban practitioners experiencing significantly higher prevalence. This study also found that increased social media use was associated with a lower likelihood of experiencing burnout, but the association did not always exist. In terms of overall burnout, the relationship between social media use and burnout was statistically significant only in urban areas. Our findings underscore the urgent need for policy makers and health care institutions to prioritize interventions addressing burnout among PHWs, particularly in underresourced and high-stress settings. Local governments could pilot platforms with moderation, allowing PHWs to showcase their work progress to the communities they serve, thereby strengthening trust and reducing emotional exhaustion. Our research also suggests that social media interventions may be particularly effective in urban settings. These findings offer actionable insights for other low- and middle-income countries navigating similar challenges. International bodies (eg, the World Health Organization) should develop digital health guidelines specific to low- and middle-income countries to help policy makers balance the benefits and risks of social media.